School Museum as A Center of The Educational Environment in The Cadet Cossack Corps - Gennadyevna Ovanesyan, Larisa; Alekseyevna Klykova, Lyudmila; Borisovna Yunusova, Elena; Gennadyevich Churashov, Andrey (Opción, 2019)
The purpose of this study is to identify and scientifically substantiate the potential of the school profile museum as a scientific and creative center for children's associations in mastering the spiritual, moral and artistic values of the folk traditional culture. The article presents a model of the educational environment, built on the experimental program of scientific and creative children's associations at the School Museum "History and Traditional Culture of the Cossacks" on the basis of the Municipal Budgetary Educatio- nal Institution of Secondary School (MBEI SES) No. 22 "Cadet Cossack School", Chelyabinsk. The urgency of the appeal to national traditions, national-cultural values as a means of training and education is substantia- ted; the attention is focused on the culture of the Russian Cossacks and as a regional component – the Orenburg Cossack army. The tasks of studying and reuniting Cossack traditions with the conditions of modern education are set, problems in creating the educational environment in the cadet corps are identified. As a result of deductive chronological and etymological analy- sis of the term “environment”, it is argued that it is necessary to centralize the study, preservation and reproduction of phenomena and facts of traditional culture at the school museum, which, by virtue of its name, is intended to become a foundation, accumulator of popular knowledge and experience turning into the activity form of children's scientific and creative associations for familiarizing the Cadets with historical and cultural heritage. It covers the goals and objectives, features of the program and the main provisions, the directions of students' activities (research, museum studies and creative), types of cadet associations, methods and educational technologies. A model of the educational environment is created and tested, in the center of which is a school museum.